POST-INDEPENDENCE RESIDENTIAL ARCHITECTURE IN THE CITIES OF THE KHOREZM REGION: DEVELOPMENT AND PERSPECTIVES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the transformation of residential architecture in the cities of Khorezm during the years following Uzbekistan’s independence. Focusing on mid- and high-rise residential buildings, the study analyzes how traditional architectural principles have interacted with modern planning approaches. Using qualitative and descriptive research methods, including visual analysis and document review, the paper identifies key trends, challenges, and future development prospects. The findings highlight a gradual shift from traditional low-rise housing toward modern multi-storey residential complexes, while emphasizing the need to preserve local identity and ensure sustainable urban development.